The Radical Politics of Nation-States: The Case of President Rodrigo Duterte - Christopher Ryan Baquero Maboloc (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2018)
The advent of terrorism in the midst of political conflict requires an understanding of local context and history. Anti-establishment leaders like President Rodrigo Duterte expose the limits of liberalism. By applying the critical distinction between “politics” and the “political,” we can imagine an alternative framework in our desire to unravel the narrative of Duterte’s communitarian style. Disruption is not simply meant to put into question the status quo. The goal of progressive leadership is to transform society in ways that will improve the difficult lives of the people. While the president’s critics say that he is authoritarian, it will be argued that radical means are needed to overcome the failures of Philippine democracy.